An Efficient Chaotic Cryptosystem for Real-time MPEG Video Encryption Algorithm using Arnold’s Cat Map and Henon Map - Bhuvaneswari, K.; Mahesh, K. (IJRDO -Journal of Computer Science Engineering, 2017)
Rapid growth in network communication, there is need development inorder to provide the securityfor sensitive data from leakages. Many algorithms were designed for past years but they are not wellproficient while concerning multimedia elements such as image and video due to high complexity ofencoded /decoded, high correlation among all the pixels. Chaos based encryption algorithm hassuggested to deal with these problems because it has desirable features of generate pseudo randomnumber, sensitivity to initial conditions. A multimedia element video is bounded of audio and imageso video encryption is to consider crucial part and critical task. The intent of proposed method is tosecure the secret video clip by encryption using Arnold’s Cat Map and Henon chaotic map. In thismethod, video is extracted into frames and equal size of chaotic sequences is generated. Originalpixel values are shuffled using cat map and its result is XORed with the chaotic sequences of HenonMap. Further, security of the implemented algorithm is evaluated by experiments on different inputvideo clips and result produced in less complexity with high security. Finally conclude that thissystem is efficacy and provides two layers of security for transmission of multimedia element video.